A comparative study on pharmacokinetics and tissue distribution of 5-hydroxy-4-methoxycanthin-6-one and its metabolite in normal and dextran sodium sulfate-induced colitis rats by HPLC-MS/MS. (3rd May 2020) - Liu, Fangle; Zhang, Qiuyu; Lin, Chaozhan; Yao, Yufeng; Wang, Meiqi; Liu, Changhui; Zhu, Chenchen
Abstract: Objectives: This study aimed to investigate the existing form of 5-hydroxy-4-methoxycanthin-6-one (PQ-A) in vivo after oral administration and the effects on its pharmacokinetics and tissue distribution by colitis. Methods: A rapid HPLC-MS/MS method was established to simultaneously determine PQ-A and its main metabolite, 1-methoxicabony-β-carboline (PQ-B), in biological samples acquired from normal and dextran sodium sulfate (DSS)-induced colitic rats administered orally with PQ-A. Then, the pharmacokinetics of both PQ-A and PQ-B, and tissue distribution of PQ-A in the above two states were analysed. Key findings: The pharmacokinetic results showed that the prototype of PQ-A was the main existing form in both physiological and pathological conditions. And significant difference between the above two status in pharmacokinetics of PQ-A was observed, such as higher exposure and longer elimination in colitis than that in normal rats. It suggested that the pharmacokinetics of medications for colitis was affected by enteritis. The tissue distribution studies displayed that PQ-A mainly accumulated in intestinal tract. Especially, the distribution of PQ-A in intestinal tract was increased obviously in colitic rats. Conclusions: These results contributed to further illuminate the ADME process of PQ-A in different status and were prospected to be the reference to the clinical application of similar medicines in pathological states.